2022
DOI: 10.3389/fnins.2022.887929
|View full text |Cite
|
Sign up to set email alerts
|

Strong Selectional Forces Fine-Tune CpG Content in Genes Involved in Neurological Disorders as Revealed by Codon Usage Patterns

Abstract: Neurodegenerative disorders cause irreversible damage to the neurons and adversely affect the quality of life. Protein misfolding and their aggregation in specific parts of the brain, mitochondrial dysfunction, calcium load, proteolytic stress, and oxidative stress are among the causes of neurodegenerative disorders. In addition, altered metabolism has been associated with neurodegeneration as evidenced by reductions in glutamine and alanine in transient global amnesia patients, higher homocysteine-cysteine di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…TpA and CpG underrepresentation at the p3-1 junction suggested that codon choices alone may not explain the scarcity of TpA and CpG since, at this position, at least TpA has no defined coding function in this frame and is the result of multiple forces, including immune pressure [ 67 , 68 ], high mutability resulting in a transition from CpG to TpG [ 69 ], selection forces [ 70 ], TpA having mRNA destabilizing effect [ 62 ], higher susceptibility of UpA to cytoplasmic RNase [ 71 ] and evading interferon-inducible protein ZAP and RNAseL as host protein responsible for sensing CpG in viral RNA.…”
Section: Resultsmentioning
confidence: 99%
“…TpA and CpG underrepresentation at the p3-1 junction suggested that codon choices alone may not explain the scarcity of TpA and CpG since, at this position, at least TpA has no defined coding function in this frame and is the result of multiple forces, including immune pressure [ 67 , 68 ], high mutability resulting in a transition from CpG to TpG [ 69 ], selection forces [ 70 ], TpA having mRNA destabilizing effect [ 62 ], higher susceptibility of UpA to cytoplasmic RNase [ 71 ] and evading interferon-inducible protein ZAP and RNAseL as host protein responsible for sensing CpG in viral RNA.…”
Section: Resultsmentioning
confidence: 99%
“…The parity plot is constructed by plotting GC bias (G3 / G3 + C3) at X-axis and AT bias (A3 / A3 + T3) at Y axis [ 50 ]. For HCV, the value of GC bias was 0.434 ± 0.007, and AT bias was 0.433 ± 0.013.…”
Section: Resultsmentioning
confidence: 99%
“…Depression is clearly a heterogeneous condition, as evidenced by the fact that two people can be diagnosed with depression but have no common symptoms. Added to this, neurodegenerative disorders too 63 can potentially contribute to depression 64 .…”
Section: Discussionmentioning
confidence: 99%